Building Ecological Awareness Through Digital Literacy: A Case Study on the Millennial Generation in Higher Education - Khusnul Khotimah; Farid Pribadi; Mulyono (Universitas Terbuka, 2024)
Abstract: This research aims to investigate the impact of ecology-based digital literacy on the formation of ecological awareness among millennial generations in higher education. Millennials, as a significant demographic group, play a key role in shaping the future of the environment. In this context, digital literacy serves as an essential tool for disseminating knowledge and motivating pro-environmental actions. The research method employed a case study approach within the higher education environment, involving a group of millennial students participating in ecology-based digital literacy. Data were collected through initial observations, pre- and post-assessment of ecological awareness, and in-depth interviews. The research results indicate that ecology-based digital literacy can enhance ecological awareness among millennials. Participants or informants demonstrated an understanding of environmental issues and skills in using digital technology to disseminate pro-environmental information. In-depth interviews revealed that ecology-based digital literacy provides additional motivation for engaging in concrete actions that support environmental sustainability. The research findings have significant implications for the development of more effective environmental education and targeted pro-environment communication strategies for the millennial generation. In conclusion, ecology-based digital literacy can be a powerful means of shaping ecological awareness among millennials and motivating them to take positive actions in support of environmental sustainability.